NS2 is required for efficient translation of viral mRNA in minute virus of mice-infected murine cells. - Naeger, L K (1993)
Detailed analysis of five NS2 mutants of the autonomous parvovirus minute virus of mice (MVMp) has revealed the following. At low multiplicities of infection, NS2 mutants killed NB324K cells as well as wild-type (wt) MVM did and grew to high titers, while in contrast they grew poorly and did not readily kill murine A9 cells. Following CaPO4 transfection of murine fibroblasts, NS2 mutant infectious clones generated approximately 10-fold less monomer replicative-form DNA than wt and no detectable progeny single-stranded DNA. On nonmurine semipermissive NB324K cells, however, these mutant plasmid clones generated near wt levels of all replicative DNA forms. After infection of highly synchronized murine fibroblasts by NS2 mutant virus at inputs equivalent to those of the wt, mutant monomer replicative-form DNA was decreased 5- to 10-fold compared with that of the wt, and progeny single-stranded DNA accumulation was decreased to an even greater extent. Both total and cytoplasmic NS2 mutant RNA was decreased, but the amount of total viral mRNA generated, relative to accumulated viral DNA in the same experiments, was similar to that seen in wt infection. The accumulation of virus-generated proteins was also decreased in NS2 mutant infection; however, the magnitude of this decrease, compared with that of wt infections, was significantly greater than the concomitant decrease in mutant-generated levels of accumulated cytoplasmic RNA, and this effect was most dramatic for VP2. There was no such disparity between the relative accumulation of mutant-generated RNA and protein in cells permissive for the growth of these mutants. These results suggest that translation of MVM viral RNA is specifically reduced in NS2 mutant infection of restrictive cells. Because the affected viral proteins are required for the efficient production of viral replicative DNA forms, these results reveal a fundamental, although perhaps not the only, role for NS2 in parvovirus infection.